2012
DOI: 10.1007/s00221-012-3173-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of intracortical inhibition in voluntary muscle relaxation

Abstract: Terminating a voluntary muscle contraction is an important aspect of motor control, and yet, its neurophysiology is unclear. The objective of this study was to determine the role of short-interval intracortical inhibition (SICI) by comparing SICIs during relaxation from a power grip versus during a sustained power grip at the matching muscle activity level. Right-handed healthy young adults gripped and relaxed from power grip following auditory cues. The relaxation period was determined as the time for the fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…4 and consistent with empirical observations [24], [25]. Inhibition decreases with increasing force [24], remains constant during hold, and there is a phasic increases at the moment of force release [25].…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…4 and consistent with empirical observations [24], [25]. Inhibition decreases with increasing force [24], remains constant during hold, and there is a phasic increases at the moment of force release [25].…”
Section: Methodssupporting
confidence: 88%
“…Its time-varying form is consistent with empirical data: it was shown that short-latency intracortical inhibition (SICI) decreases with increasing grip force [24] and increases with muscle relaxation [25]. This increase with relaxation was modeled as a phasic inhibition during release: in the absence of this signal, variations of I_Gain did no longer affect release duration.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This activity in the motor cortex is inhibitory in nature, as evidenced by increased intracortical inhibition in M1 during muscle relaxation (Buccolieri et al, 2004a, Motawar et al, 2012). This increased intracortical inhibition may be responsible for decreased spinal motor excitability during muscle relaxation in the soleus muscle in young adults (Schieppati and Crenna, 1984, Schieppati et al, 1985, 1986).…”
Section: Introductionmentioning
confidence: 99%